2022
DOI: 10.12998/wjcc.v10.i8.2363
|View full text |Cite
|
Sign up to set email alerts
|

eHealth, telehealth, and telemedicine in the management of the COVID-19 pandemic and beyond: Lessons learned and future perspectives

Abstract: In this article, we discuss evidence supporting the effective implementation of eHealth, telehealth, and telemedicine during the coronavirus disease 2019 pandemic, with a view towards its permanent future integration in healthcare. We performed a literature search for articles describing the use of telehealth/ telemedicine in the pandemic context using five databases. The articles selected describe the use of telemedicine as its advantages in terms of practicality and cost-effectiveness. This synthesis of arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Moreover, it found that telemedicine permits the examination of a patient's health, while also digitally educating individuals about physical examination changes and symptoms that should provoke a dialogue with their doctors. In another literature search, Giacalone et al ( 10 ) examined papers addressing the use of telehealth/telemedicine in the COVID-19 environment. They have discovered that the broad adoption of telemedicine services faces a number of obstacles that are mostly bureaucratic and regulatory in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it found that telemedicine permits the examination of a patient's health, while also digitally educating individuals about physical examination changes and symptoms that should provoke a dialogue with their doctors. In another literature search, Giacalone et al ( 10 ) examined papers addressing the use of telehealth/telemedicine in the COVID-19 environment. They have discovered that the broad adoption of telemedicine services faces a number of obstacles that are mostly bureaucratic and regulatory in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends were observed in the present study, in which a significant percentage of participants used self-medication. Teledentistry is set to continue to expand, especially to remote or rural areas where access to specialist oral healthcare services is difficult [ 24 ] and there is also a urgent need to integrate dental software with teledentistry to make patient data management less troublesome [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…What this change represents for the future of HF management and the provision of HF services in outpatient scenarios worldwide remains warmly debated[ 108 ].…”
Section: Telemedicinementioning
confidence: 99%